A method for measuring the movement of Gravity center of body of golf swing based on Kinect Sensor - Wang, Xiangmin; Chen, Jie (International Journal of Engineering and Computer Science, 2018)
In this paper, we propose a method to measure the movement of skeletons of body of golf swing by the use of a Kinect sensor, and an algorithm to calculate the track of motion of the Gravity center of body. Because swing speed is usually fast, tracking a golf swing with one Kinect sensor causes less skeleton data to be sampled. Taking into account the continuity and trajectory characteristics of the skeleton data of the golfer, a reasonable interpolation method can effectively compensate for the lack of data. By comparing with the test data of the balance pedal, the measurement method is valid and accurate.